Evolution of ocean circulation and water masses in the Guaymas Basin (Gulf of California) during the last 31,000 years revealed by radiolarians and silicoflagellates in IODP expedition 385 sediment cores - Velázquez-Aguilar, M.; Pérez-Cruz, L.; Urrutia-Fucugauchi, J.; Marsaglia, K. M.; Coria-Monter, E.; Monreal-Gómez, M. A.; Teske, A.; Höfig, T. W.; Aldama-Cervantes, A.; Jiang, S. D. (Frontiers in Earth Science, 2024)
The high-resolution analysis of radiolarians and silicoflagellates in sediments from Holes U1545A and U1549A drilled during IODP Expedition 385 in the Guaymas Basin, in the Gulf of California provides detailed insights into the evolution of ocean circulation and water masses, and its relation to Eastern Tropical Pacific Ocean climate conditions, over the past 31,000 cal years BP (based on AMS radiocarbon dates). In the pre-Last Glacial Maximum, the Guaymas Basin experienced alternating circulation patterns of California Current Water (CCW) and Gulf of California Water (GCW), with an extended presence of the Pacific Intermediate Water (PIW) owing to: amplified jet streams; southern movement of the California Current System (CCS) and the incursion of CCW into the gulf; and increased North Pacific Intermediate Water (NPIW) formation. The Last Glacial Maximum witnessed the incursion of CCW due to the stronger CCS. The dominance of the PIW indicates the expansion and formation of NPIW. The Heinrich-I event as manifested in the core record, displays two distinct patterns, one suggesting GCW-like dominance and the other, the occurrence of CCW. The Bølling-Ållerød interstadial featured the entry of Tropical Surface Water (TSW), GCW, and CCW, linked with the northward migration of the Intertropical Convergence Zone. In the Younger Dryas, CCW dominated, transitioning to GCW as colder climatic conditions and more intense CCS. The Holocene displayed alternating periods of TSW and GCW, with a modern monsoon regime from 7,600 to 1,000 cal years BP. From 1,000 cal years BP to the present the ITCZ shifted to the south.